Decitabine-Intensified Modified Busulfan/Cyclophosphamide Conditioning Regimen Improves Survival in Acute Myeloid Leukemia Patients Undergoing Related Donor Hematopoietic Stem Cell Transplantation: A Propensity Score Matched Analysis - Ziying Li; Wei Shi; Xuan Lu; Hui Lu; Xiena Cao; Liang Tang; Han Yan; Zhaodong Zhong; Yong You; Linghui Xia; Yu Hu; Huafang Wang (Frontiers in Oncology, 2022)
To identify the benefit of decitabine (Dec)-intensified myeloablative conditioning on the outcomes of patients with acute myeloid leukemia (AML) after related donor hematopoietic stem cell transplantation (HSCT), we performed a retrospective matched‐pair study from a pool of 156 patients to evaluate Dec [20 mg/m2/day intravenously (i.v.) on days −11 to −7]-intensified modified busulfan/cyclophosphamide (mBuCy) conditioning regimen vs. mBuCy regimen in 92 AML patients, with 46 patients in each cohort. The cumulative incidence of grade II–IV acute graft-versus-host disease (aGVHD) was lower in the Dec group (15.2% ± 0.3% vs. 32.6% ± 0.5%, P = 0.033). Compared with mBuCy group (15.5% ± 0.3%), a significantly higher proportion of limited chronic GVHD (cGVHD) in Dec group (35% ± 0.6%) was observed (P = 0.025). Dec-intensified mBuCy conditioning was associated with better 2-year overall survival (OS) and GVHD-free relapse-free survival (GRFS) (81% ± 6.2% vs. 59.4% ± 7.5%, P = 0.03; 58.7% ± 8.1% vs. 40.9% ± 7.3%, P = 0.042; respectively). Our results also elucidated that the Dec group had better 2-year OS and lower 2-year cumulative incidence of relapse (CIR) in patients acquiring haploidentical HSCT than that of the mBuCy group (84.8% ± 7.1% vs. 58.2% ± 10.3%, P = 0.047; 17.9% ± 0.8% vs. 40.0% ± 1.0%, P = 0.036; respectively), which did not increase the treatment-related mortality and regimen-associated toxicities. Dec-intensified myeloablative regimen and high-risk stratification were the variables associated with OS, leukemia-free survival (LFS), and GRFS in multivariate analysis. In high-risk patients, no differences were found in CIR, OS, LFS, and GRFS between the two groups. These data indicated that Dec-intensified mBuCy conditioning regimen was associated with better survival than mBuCy regimen in AML patients, especially in patients undergoing haploidentical HSCT.